Experimental transmission of Corn Stunt Spiroplasma Present In Different Regions of Argentina - Carpane, P. (2006)
The aim was to transmit Corn stunt spiroplasma (Spiroplasma kunkelii Whitcomb) using field-collected Dalbulus maidis insects (Hemiptera-Cicadellidae), and diseased plants from places in the subtropical and temperate regions of Argentina. Field-collected D. maidis populations transmitted the spiroplasma in 39% of the cases when a density of five insects per plant was used. Transmissions were obtained from diseased plants collected in two subtropical locations. In all the symptomatic plants, the presence of spiroplasma was detected by serology and confirmed with PCR. The development of the symptoms and the pathogen titer varied between plants infected with insects from the same location, leading to the identification of two plant groups: one with severe symptoms and high pathogen titer, and the other with mild symptoms and lower titer, showing a direct relation between pathogen titer and the severity of symptoms